(untitled) (Italian Review of Legal History, 2020)
The plague that broke out in Milan between 1576 and 1577, during the episcopate of Carlo Borromeo, is worthy to be investigated as far as regards the legal measures adopted by the Milanese government to deal with the epidemic, within a broader reflection on the relationship between policy and society in the Early Modern period. As a matter of fact, the provisions enacted during the San Carlo plague, for their “extraordinary” character, allow to carry out an overall consideration about government practices during the emergencies, in balancing out public health and individual freedom. After the “black death” of 1348, governments established temporary magistracies in order to manage public health. During the 15th and 16th centuries, these magistracies became permanent, resulting in an increasing intervention of the State in the matters of public health. Also in Milan, these officials were initially limited to the periods of plague, but, in the 15th century, they were trasformed in permanent assignments. Officially established as a collegiate magistracy in 1534 by Francesco II Sforza, this magistracy was regulated in the Novae Constitutiones. Chaired by a senator and composed of two quaestors, two collegiate doctors, a legal auditor and a secretary, the officium Praefectorum Sanitatis Dominii Mediolani enacted and enforced the laws aimed at safeguarding public health throughout the State. In order to fight the plague between the Middle Ages and the Early Modern period, governments – through the magistracies of health – passed “exceptional” rules (since they related to particular situations or specific cases, such as wars, and derogated from the general principles of the legal system). Authors of juridical treatises on plague connected these measures to the legal categories of necessitas and of the publica utilitas, that allowed to justify the action of political authorities in cases of emergency, even when derogating from ordinary rules. Remedies adopted by political authorities in order to prevent the spread of epidemic restrained the freedom of movement: when a plague broke out, governments – according to common practices – control movements of people and goods in order to reduce contagions, through increasingly restrictive measures as the situation worsened. Since population used to oppose such restrictions, the provisions passed by governments aimed not only at protecting public health, but also at controlling what we now call “public order” within the city. In handling with plague epidemics, governments made broad use of criminal law with an intimidating function. Thus, the violation of the anti-contagion measures was strictly punished. Penalties, that were to be applied according to the arbitrium of the magistracy, worsened when people did not abide by the rules. According to Ludovico Antonio Muratori, who at the beginning of the 18th century wrote a treatise on the “government of the plague”, the emergency required government to resort to exemplary penalties in order to ensure compliance with the rules, Death penalty therefore was inflicted with a certain frequency. At the same time, when dealing with such an “invisible enemy”, governments resorted to pecuniary rewards. By promising to the accusers a part of the fine imposed on the transgressors, the authorities encouraged people to collaborate in repressing the violation of health laws. During the San Carlo plague, the Milanese magistracy of health prohibited access of people and goods from infected or even suspicious areas, expelled beggars and vagrants from the city, isolated infected people and, finally, quarantine women and children and then all the population in order to prevent and contain the contagions.